Empowering Engineering Ethics: Integrating Project-Based Learning for Holistic Student Development in VLSI Education - Madhavi, Kalasapati Bindu; Mosherani, Velicharla; Anadakumar, Annavarapu (Journal of Engineering Education Transformations, 2025)
Integrating value education into Electronics and communication engineering program and Electrical and Electronics engineering program is essential for developing students' ethical, social, and emotional maturity, enabling them to navigate personal and professional scenarios with integrity and empathy. This paper incorporates the PBL into VLSI courses within a value educational framework, that offers a comprehensive approach to student development. It is not only enhances technical proficiency but also cultivates essential life skills and values, promoting engaged learning and holistic growth. Project-Based Learning (PBL) is an effective strategy for achieving this integration, transforming the educational landscape by fostering both technical skills and essential life principles. PBL engages students in hands-on projects that simulate real-world challenges, requiring collaboration, critical thinking, and innovative problem-solving, particularly in the field of VLSI. This active learning approach shifts the educational experience from passive reception to active engagement, allowing students to take control of their learning journey. This approach ultimately prepares socially responsible engineers ready to make positive contributions to society. Engineering ethics plays a crucial role in ensuring that technological advancements benefit society and minimize harm. In VLSI, ethical considerations can affect safety, privacy, and environmental sustainability. Integrating ethics into engineering education equips students to navigate these challenges responsibly.